1977
DOI: 10.1021/bi00644a031
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of hemoglobin with red blood cell membranes as shown by a fluorescent chromophore

Abstract: Hemoglobin quenching of the fluorescence intensity of 12-(9-anthroyl)stearic acid (AS) embedded in the red blood cell membrane occurs through an energy transfer mechanism and can be used to measure the binding of hemoglobin to the membrane. The binding of hemoglobin to red cell membranes was found to be reversible and electrostatic in nature. Using a theory of energy transfer based on Förster formulation, the quantitative data for the binding were derived. The number of binding sites was found to be 1.4 +/- 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
148
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(152 citation statements)
references
References 17 publications
4
148
0
Order By: Relevance
“…When Hb A, C, or S was added to AS-labeled 10 Fig. 3 show that the binding constant of Hb C at pH 6.8 (35 X 106 M-') was slightly lower than the binding constant for Hb A at pH 6.0, calculated previously to be 80 X 106 M- (6).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…When Hb A, C, or S was added to AS-labeled 10 Fig. 3 show that the binding constant of Hb C at pH 6.8 (35 X 106 M-') was slightly lower than the binding constant for Hb A at pH 6.0, calculated previously to be 80 X 106 M- (6).…”
Section: Resultsmentioning
confidence: 62%
“…In earlier studies we and others (6)(7)(8) have demonstrated binding of hemoglobin A to erythrocyte membranes. The method used in those and in the present studies utilized a fluorescent chromophore embedded in erythrocyte membranes prepared by hypotonic lysis: when hemoglobin approaches the chromophore, 12-(9-anthroyloxy)stearic acid, the fluorescence is quenched by an energy transfer mechanism.…”
Section: Introductionmentioning
confidence: 75%
“…If one makes the parsimonious and plausible assumption that the point mutation in globin is the only inherited genetic abnormality affecting CC red cells, it is likely that the abnormal globin interacts directly with the cation transport system or its regulators in such a way as to produce the observed transport abnormalities or with a nmembrane component not normally involved in cation transport. It has been shown that hemoglobin binds to the erythrocyte membrane (25,26) and that hemoglobin C binds with a higher affinity than hemoglobin A at neutral pH (27,28). An important site of interaction with the membrane is the N-terminal segment of band 3, which contains a sequence of 23 residues of which 14 are either glutamate or aspartate (29).…”
Section: Discussionmentioning
confidence: 99%
“…Hb is known to bind to membrane Band 3 protein especially under hypoxic conditions [28]. HbS and HbC have a higher affinity for band 3 than HbA [24,25].…”
Section: Membrane Damage Associated With In Vivo Heme Degradationmentioning
confidence: 99%